Factors Influencing Social Commerce Purchase Decision Via Mobile Apps In The New Normal Period - Imaduddin; Andi Faisal Bahari; Muhammad Ashoer; Zaenal Arifin Sahabuddin (Institute of Computer Science (IOCS), 2022)
During the new normal, social commerce (s-commerce) activities have been emerging expeditiously as it offers solutions to fulfill Indonesians’ needs and wants. To analyzed this concurrent phenomenon, we have identified exogenous constructs (Word-of-Mouth (WoM), trust, and advertising) based on previous research mapping and tested their impact on consumer purchasing decisions via s-commerce (Instagram) apps. Subsequently, a online survey was selected as a data collection method to minimize physical contacts between people. A link of electronic questionnaire was generated and then distributed directly to all active Instagram users in Indonesia via Whatsapp and email. Purposive sampling technique was used to select 208 respondents who had basic knowledge of s-commerce concepts and practices and had conducted direct transactions at least twice. According to the PLS-SEM output, WoM and trust has a positive and significant effect on s-commerce purchasing decisions, whereas advertising has no effect. These findings offer the most up-to-date insights for e-commerce companies and related social media to reform their marketing strategies in the new normal to maintain consumer satisfaction and loyalty.